(untitled) (International Journal of Culture and Art Studies, 2025)
The art of humor often leaves a lasting impression, especially when it connects to joyful memories. Nostalgia refers to a longing for the past, often tied to moments of laughter and happiness. This study analyzes Warkop DKI Reborn: Jangkrik Boss Part 1 as a modern reflection of nostalgia for the original Warkop DKI films, focusing on the humor that defined the series. The study also examines YouTube comments to understand how audiences perceive the film’s humor. A qualitative approach is used, with data from Warkop DKI - Chips (1982) Full Movie on the @LetsuGauki YouTube channel and WARKOP DKI Reborn | Jangkrik Boss Part 1 | Kalau Mau Dosa Sekalian Banyak, uploaded by Falcon YouTube. The analysis draws on the theories of Nostalgia for the Present from Salmose (2019), Mise en Scene from Manon de Reeper (2016), and Media Studies from Ott (2014). The findings indicate that the characters, costumes, humor, and settings in both the original and reborn films evoke a deep sense of nostalgia among Indonesians, demonstrating how the art of humor continues to bridge generations and maintain cultural relevance.